A CONTINUUM ANALYSIS OF STUDENTS’ TRANSLATION SKILLS AT THE FIFTH SEMESTER OF ENGLISH DEPARTMENT MAKASSAR MUHAMMADIYAH UNIVERSITY - Andi Nuzul Hikmah Buana; M. Basri Dalle; Farisha Andi Baso (Universitas Muhammadiyah Makassar, 2019)
The objective of this research to identify students’ translation skills based on Continuum and to find out the students’ difficulties in translation at the fifth semester students English Department Makassar Muhammadiyah University. This research applied the descriptive qualitative research for the data collection by using translation paper test consisting 3 short paragraph with title “Food, Nutrition and Health” and an open-ended questionnaire consisting five numbers. The data was taken from 30 students in 10 class by using random sampling technique. The result of this research was in general the students have a good translation skills. Although the students result is not consistent yet. It can be seen from the students translation paper test result. The translation result understandable in some parts. Then the difficulties that students faced in translation are 2 aspects, first is diction and the second is meaning. They rarely choose appropriate words, because they took wrong word and also got the incorrect meaning. Besides the result from the translation paper test it can be seen in the questionnaire, there are some students stated that the difficulties in translation is the choose appropriate words.